Synthesis, characterization, and application of agar/alginate/k-carrageenan hydrogel blends for water retention in soil - De Chavez, Reynaldo C. Jr
Providing a reliable water source for crops on farmlands has always been a challenge in many arid regions of the country because of various circumstances. Due to these, potential technological aid should be explored -- one of which is soil amendment using hydrogels. However, most commercial hydrogels for soil application could be harmful to the environment and toxic because of their synthetic compositions. Thus, in this study, natural hydrogel blends of agar, alginate, and K-carrageenan were produced. The three components were mixed in different proportions according to the augmented simplex lattice matrix design. The hydrogels were characterized using Fourier-transform Infrared Spectroscopy (FTIR) and Scanning Electron microscopy (SEM). The swelling ratios and water uptake mechanism of the hydrogels were then investigated and mapped to the mixture design. Increasing the agar composition generally results to lower swelling ratio that is predominantly governed by diffusion. Increasing K-carrageenan composition, on the other hand, leads to higher swelling ratio that is predominantly governed by macromolecular relaxation. The hydrogels were then applied to dried loam soil which was subsequently watered. The water depletion of the soil was investigated within a controlled heated environment for a week and the results were mapped to the mixture design. The hydrogel application is able to decrease the water depletion rate of the soil by a maximum of 17.8 percent with strong correlation to the agar-alginate interaction.